2011
DOI: 10.1074/jbc.m110.188664
|View full text |Cite
|
Sign up to set email alerts
|

Attractant Binding Induces Distinct Structural Changes to the Polar and Lateral Signaling Clusters in Bacillus subtilis Chemotaxis

Abstract: Bacteria employ a modified two-component system for chemotaxis, where the receptors form ternary complexes with CheA histidine kinases and CheW adaptor proteins. These complexes are arranged in semi-ordered arrays clustered predominantly at the cell poles. The prevailing models assume that these arrays are static and reorganize only locally in response to attractant binding. Recent studies have shown, however, that these structures may in fact be much more fluid. We investigated the localization of the chemota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…In several prokaryotic organisms taxis receptors assemble into large, mixed clusters [74-81] which facilitate signal integration, large signal amplification and high sensitivity [76,82-85]. Due to this cluster formation it is not possible to deduce whether certain Htrs directly interact with a Che protein from copurification experiments.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several prokaryotic organisms taxis receptors assemble into large, mixed clusters [74-81] which facilitate signal integration, large signal amplification and high sensitivity [76,82-85]. Due to this cluster formation it is not possible to deduce whether certain Htrs directly interact with a Che protein from copurification experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Dynamic changes in the signaling clusters have recently been directly observed in B.subtilis [81]. Immunofluorescence microscopy showed that attractant binding caused a decrease in the number of observable polar receptor clusters and an increase in the lateral receptor clusters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An additional facet of CheV worth noting concerns mobility. In a previous study investigating the spatial localization of the chemotaxis proteins in B. subtilis, we observed changes in the localization of CheV following the addition and subsequent adaption to asparagine (Wu et al ., ). Specifically, CheV was found to associate more strongly with the receptors and CheA at the cell poles following the addition of asparagine than with the lateral receptors, where CheA and CheW are scarce.…”
Section: Discussionmentioning
confidence: 97%
“…B. subtilis has three systems that foster adaptation: a system involving receptor methylation [5], [9], a system involving phosphorylation of CheV [10], [11], and a system involving CheC, CheD, and CheYp [12], [13]. CheV is homologous to the coupling protein CheW except that it also has an N-terminal response regulator domain [14], [15].…”
Section: Introductionmentioning
confidence: 99%